Physiological aspects of weight loss in obesity - Patel, Kishor Kantilal (2011)
Obesity continues to be a major cause of morbidity and mortality and worldwide prevalence rates continue to rise. The cornerstone for treating obesity remains diet and lifestyle, with the ultimate goal being normalising those parameters that are associated with ill health, for example hyperinsulinaemia and insulin resistance. Because obesity predominantly develops due to a mismatch between energy intake and utilisation, this thesis looked at the effects of dietary interventions upon Resting Energy Expenditure (REE) and substrate oxidation. In addition, the impact of popular dietary interventions upon body composition and insulin resistance was examined. When phenotypic characteristics were investigated before and after weight loss by using hypocaloric diets, which differed in fat and carbohydrate content, Fat-Free Mass (FFM) and Fat Mass (FM), were strong predictors of REE before and after the intervention and weight loss rather than the specific dietary intervention, significantly predicted post intervention REE. Fasting fat oxidation was found to be lower in obese subjects and they had a lower postprandial response to a high fat challenge. This implied that a diet high in fat is more likely to promote a positive energy balance an ultimate weight gain. The final study compared 4 popular dietary interventions. Each was equally effective at achieving clinically significant weight loss and improvements in insulin sensitivity. Although none was significantly more superior, there was a trend supporting three of the diets (Atkins’, Weight Watchers and Rosemary Conley) above the other (Slim-Fast) and it was the pattern of weight loss, i.e. mainly loss of FM, which proved beneficial with regards to improving insulin sensitivity. In summary, this thesis confirms that REE is mainly predicted by FFM and FM and that there is diminished fat oxidation on obese subjects. What this thesis also adds to previous research that it if a specific diet can improve the pattern of weight loss, this can be clinically beneficial.